Emulating the noble morals of the Prophet: forming the character of teenagers from an early age - Novita kurnia ilahi; Rizkiah wulandari; M. Mahbubi (Almustofa Journal of Islamic Studies and Research, 2025)
Abstract Instilling noble morals from an early age is the main foundation in the formation of Islamic adolescent character. The Prophet Muhammad SAW as a perfect role model, has shown commendable morals in all aspects of daily life, such as honesty, responsibility, compassion, politeness, and patience. This article discusses the importance of emulating the morals of the Prophet in the daily lives of adolescents, and how these values ​​can be internalized through Islamic Religious Education (PAI). With a contextual learning approach and role models, moral education is expected to be able to shape adolescent personalities who have integrity, empathy, and behave according to Islamic teachings. This study emphasizes that the habituation of noble morals is not only the responsibility of the school, but also the family and supportive social environment. Thus, the character of Islamic adolescents can be formed strongly as provisions to face the challenges of the times